POPULASI HAMA Paraeucosmetus pallicornis Dallas (HEMIPTERA : LYGAEIDAE) PADA TANAMAN PADI SAWAH DI KABUPATEN MINAHASA SELATAN - Nataldo Sigalingging; Moulwy Frits Dien.; Robert William Tairas (Universitas Sam Ratulangi, 2017)
ABSTRACTResearch on pest populations of Paraeucosmetus pallicornis Dallas has been carried out on rice plantation cultivation in South Minahasa District. The aim of this research is to know the population of P. pallicornis pest at various altitude places in South Minahasa District. The study was conducted for three months from September to November 2016. The research used survey method while sampling was done by Stratified Sampling consisting of three altitude places from above sea level (asl) that is 0 - 200 meters asl, > 200 - 400 meters asl, and > 400 meters asl in rice field in South Minahasa District, North Sulawesi Province. At each altitude stratum three terraced plots were determined as sample locations. Sampling was done 3 times, ie at plants aged 7, 9, and 11 weeks after planting (wap). Observation of population of P. pallicornis was done by using insect cages measuring 90 cm long, 90 cm wide and 150 cm high made of bamboo as a skeleton and covered with gauze. The results showed that the average pest population of P. pallicornis at various altitude places in South Minahasa District, the highest was found at altitude > 200 - 400 meters asl reach 52.88, then altitude 0 - 200 meters asl 34.33 and altitude > 400 meters asl 17.55. The average pest population of P. pallicornis at the highest plant age range was found at 11 wap to 49.66, then 9 wap 30.99 and 7 wap 24.20.Keywords : Populations, Altitude places